Static and Dynamic Characteristics Analysis on Frame Beam Reinforced with Carbon Fiber Reinforced Plastic Based on ANSYS - YU Wenhuan; MI Kaihua; ZHAO Ping (Renmin Zhujiang)
To study the static and dynamic characteristics on frame beam reinforced with carbon fiber reinforced plastic,a frame beam for example,the three-dimensional finite element model was established by the FEM soft-ware ANSYS,when the frame beam in unreinforced,ordinary carbon fiber reinforced and prestressed carbon fiber reinforced has respectively carried on the static analysis,modal analysis and time history analysis.Research showed that carbon fiber reinforced plastics could significantly improve the ultimate bearing capacity of the frame beam,but could be reduced to a corresponding the ductility of the frame beam;prestressed carbon fiber reinforced had great effects on the natural frequency of vibration of frame beam and greatly improved the rigidity of frame beam;ordinary carbon fiber reinforcement could hardly improve the seismic performance of frame beam,whereas the prestressed carbon fiber reinforced plastics could significantly improve the level of frame beam of horizontal seismic performance,the seismic design criterion of “strong column and weak beam” should be followed in design.